Concurrent Renorrhaphy During Renal Mass Excision in Laparoscopic Nephron-Sparing Surgery: A Novel Surgical Technique - Nurullah Hamidi; Tuncel Uzel (Urology Research and Practice)
Objective: Laparoscopic nephron sparing surgery (NSS) can be performed by mainly 2 methods, offclamp or on-clamp. Continuous bleeding during the off-clamp method may impair the clear visualization of the border between the tumor and parenchyma, even though it is done safely in experienced hands. Therefore, some surgical modifications may be needed during mass excision and renorraphy. In this video brief, we aimed to present a new off-clamp NSS technique and our case series. The difference of this technique from others is that renorrhaphy was performed during mass excision concurrently to reduce the amount of bleeding.